Mediators of self-destructive behaviors in women survivors of childhood sexual abuse: A structural model - Fritchel, Kellie Bree (2008)
The purpose of this project was to examine the predictors of risky sexual behaviors and poor eating behaviors for women who experienced childhood sexual abuse, including family hardiness, and depression in a structural equation model. A second group of those who had not been sexually abused as children was also tested using the same structural equation model